Performance of complementor’s complementary goods on platform ecosystems: the perspective of individual complementors' complementary goods development behavior - Xiaoxiao Zhou; Yuki Inoue (Future Business Journal)
Abstract The purpose of our study was to examine how individual complementors' development behaviors (specifically, diversity- and distinctiveness-oriented development behaviors) impact the performance of complementary goods on the platform. To achieve this, we employed fixed-effects regression analysis and utilized panel data obtained from the free music platform “DOVA.” This study examines two aspects of the performance of complementor’s complementary goods: the highest performance related to the success of the platform ecosystem and the lowest performance related to platform ecosystem sustainment. The findings indicate that a high focus on diversity-oriented development behavior is positively correlated with the complementor's highest performance and negatively correlated with complementor's lowest performance. Additionally, distinctiveness-oriented development behavior also positively correlated with complementor's highest performance. However, low distinctiveness-oriented development behavior is negatively correlated with complementor's lowest performance. We reveal desirable development behaviors for complementary goods related to both content innovation and platform ecosystem sustainability. Based on these understandings, platform owners can target platform governance.